LO94: Prognostic value of neuron-specific enolase (NSE) for prediction of post-concussion symptoms following a mild traumatic brain injury: a systematic review. (15th May 2017) - Mercier, E.; Tardif, P.; Cameron, P.; Émond, M.; Moore, L.; Mitra, B.; Ouellet, M.; Frenette, J.; De Guise, É.; Le Sage, N.
Abstract : Introduction: Mild traumatic brain injury (mTBI) is an understudied worldwide health problem and a socio-economic burden that remains a major cause of morbidity. However, there is no prognostication tool to help clinicians predict the occurrence of post-concussion symptoms. This systematic review aimed to determine the prognostic value of neuron-specific enolase (NSE) to predict post-concussion symptoms following a mTBI in adults.Methods: The protocol of this systematic review was registered with the International Prospective Register of Systematic Reviews (PROSPERO) database (registration number CRD42016033683). Seven databases (CINAHL, Cochrane CENTRAL, EMBASE, MEDLINE, PsycBITE, PsycINFO, Web of Knowledge/Biosis) were searched for cohort studies evaluating the association between NSE levels and post-concussion symptoms assessed at least seven days after the mild TBI. Grey literature was also screened using databases on dissertations and theses as well as abstracts from relevant congresses. Two researchers independently screened studies for inclusion, extracted data, and appraised their quality using the Quality in Prognostic Studies (QUIPS) tool from the Cochrane Collaboration Group.Results: Our search strategy yielded a total of 23, 298 citations from which eight cohorts presented in 10 studies were included. Studies included between 45 and 141 patients (total=608 patients). The most frequently assessed outcomes were post-concussion syndrome (PCS) (13 assessments), neuropsychological disorders (10 assessments), return to work or sick leave (2 assessments) and Glasgow Outcome Scale (GOS) (2 assessments). No association was found between an elevated NSE serum level and the occurrence of PCS. Of the 33 outcomes assessments performed, only three showed an association between a higher level of serum NSE and a post-concussion symptom (alteration of at least three cognitive domains at 2 weeks, standardised physician assessment at 6 weeks and headache at 6 months following a mild TBI). Included studies' overall risk of bias was considered moderate.Conclusion: Results of this systematic review conclude that based on current levels of evidence, serum NSE levels alone do not provide prognostic information on persistent or early post-concussion symptoms after a mTBI.